The Effects of Using Short Stories on the Development of Students’ Reading Comprehension of SMAN 8 Selayar - Megawati Megawati; Nurdin Noni; Maemuna Muhayyang (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aims to find out the development of students’ critical reading comprehension through short stories. The method used a quantitative design with a pre-experimental research design with a sample of 29 students from class XI MIA using a cluster random sampling technique. In obtaining the data, the researchers used the pre-test as an instrument. The results of the data analysis showed that by using short stories, the students’ critical reading comprehension developed. It can be proven by the t-test value was lower than P (0.000 < 0.05) which means that H0 this research was rejected and H1 was accepted. So, it can be concluded that the use of short stories develops students’ critical reading comprehension among the eleventh-grade students of SMA Negeri 8 Selayar.